Physiological and metabolic responses to low-volume sprint interval exercises: influence of sprint duration and repetitions - Yamagishi, T., Iwata, S., Otsuka, S., Ichinose, H., Kawakami, Y. (Medicine & Science in Sports & Exercise, 2024)
Purpose This study aimed to determine physiological and metabolic responses to two different sprint interval exercises (SIE) matched for total sprint duration and sprint-to-rest ratio.